In the Fiftieth Anniversary of the International Theological Commission. Contributions to Fundamental Theology, Christology and Ecclesiology - Galli, Carlos María (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
In theology we gratefully reap what others sowed through tears and generously sow what others will reap. 2019 marked the 50th anniversary of the International Theological Commission (ITC) created by Saint Paul VI at the request of the first assembly of the Synod of Bishops to continue the collaboration lived during the Second Vatican Council. The CTI testifies to a diachronic and synchronic communion with corsi e recorsi. Some contributions to systematic theology given in its 30 documents are highlighted. It takes a general look at the style of the Commission and the method of work; points out the great contributions to fundamental theology and to the central mysteries of the faith in dialogue with current trends; draw the synodal figure of the theologian.
Keywords: teología de los misterios de Dios, Cristo y la Iglesia; fiftieth anniversary; theological community; synodal method; fundamental theology; theology of the mysteries of God, Christ and the Church